Infrared spectroscopic study of triacetyl‒β‒cyclodextrin and its inclusion complex with nicardipine. Issue 3 (2004) - Bratu Bratu, I. I.; Veiga Veiga, F. F.; Fernandes Fernandes, C. C.; Hernanz Hernanz, A. A.; Gavira Gavira, J. M. J. M.
Abstract : Infrared spectra of inclusion compounds of triacetyl‒ β ‒cyclodextrin with nicardipine hydrochloride were compared and analysed with those corresponding to their physical mixture and the pure compounds, respectively. Different O–H stretching vibrations, assigned to water molecules, were located in the Fourier Transform Infrared (FT IR) spectra of triacetyl‒ β ‒cyclodextrin, and its inclusion complex with nicardipine obtained by spray‒drying (SD) method. Water molecules involved in various hydrogen bonds environments change their status during complexation process. Evidences are observed of the formation of the complex especially in the spectral regions of the amino and carbonyl stretching vibrations.